Aladdin - Mitchell, H. Q. (London : MM Publications, 2003)
A retelling of the classic story of Aladdin, a young boy who discovers a powerful genie and manages to thwart an evil magician's tricks.
2
K-3.
K-3.
Keywords: Readers (Elementary).; Readers; Reading materials